2022
DOI: 10.1097/ju.0000000000002837
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Conversion From Partial to Radical Nephrectomy: An Analysis of Incidence, Etiology, and Risk Factors

Abstract: Purpose:Conversions from partial to radical nephrectomy are uncommon and reports on this topic are rare. In this study we present a detailed analysis of conversions from partial to radical nephrectomy in a single-institutional contemporary experience and provide an analysis of preoperative risk factors.Materials and Methods:Patients who underwent converted (cases) and completed (controls) partial nephrectomy from 2000 to 2015 were matched 1:1 for analysis. Perioperative imaging was reviewed and RENAL (for radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The 4.2% rate of conversion to RN reported in our study is comparable to other rates reported in literature, which have ranged from 0.14% to 14%. [11][12][13][14][15][16] Identifying patients who are at a high risk of conversion to RN may help inform preoperative counseling. Our study identified that patients with larger and high-complexity tumors were more likely to undergo conversion to RN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 4.2% rate of conversion to RN reported in our study is comparable to other rates reported in literature, which have ranged from 0.14% to 14%. [11][12][13][14][15][16] Identifying patients who are at a high risk of conversion to RN may help inform preoperative counseling. Our study identified that patients with larger and high-complexity tumors were more likely to undergo conversion to RN.…”
Section: Discussionmentioning
confidence: 99%
“…score, hilar tumors/renal sinus invasion, laparoscopic PN, intraoperative bleeding, positive surgical margins, and advanced pathological tumor stage. 11,12,14,15 Assessment of tumor complexity is a necessary component to identify tumors at high risk for conversion and other complications. 19,20 Dahlkamp et al demonstrated the value of R.E.N.A.L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons to convert a robotic partial nephrectomy (RPN) to a radical nephrectomy (RN) include concern for compromising oncologic outcomes, anatomic complexity, hemorrhage, and challenges with required renorrhaphy. 1 We continue to seek clarity behind these reasons in order approach RPN as safely as possible.…”
Section: Editorial Commentmentioning
confidence: 99%
“…Tsivian et al (page 960) from Rochester, Minnesota, from a single-center prospectively collected data set, present the largest case-control study evaluating patient and tumor factors that might help predict the need for conversion from partial to radical nephrectomy. 3 Given past conflicting reports, this is a significant unmet need, as having a better understanding of the variables that might influence chance of conversion are important to provide patients more accurate expectations of potential outcomes. Although the requirement for conversion decreased over time, on multivariable analyses male sex, comorbidities, and posterior and middle (on anteroposterior axis) as well as hilar location were associated with conversion, even after adjusting for tumor size.…”
Section: Factors Leading To Conversion For Partial To Radical Nephrec...mentioning
confidence: 99%